Curium(III) luminescence spectroscopy as a tool for species determination - Schmidt, Moritz; Skerencak-Frech, Andrej; Panak, Petra; Huittinen, Nina (Chemical Society reviews, 2025)
Curium is an artificial transuranic element with atomic number 96. It is typically found in its +III oxidation state, which is stabilized by a 5f7 electron configuration. CmIII exhibits intense luminescence from its first excited to its ground state in the red part of the visual spectrum. Due to the nature of the 5f electron shell, this luminescence is sensitive to changes in the chemical environment of the CmIII probe, while being detectable in the trace concentration range. This unique combination has established CmIII luminescence spectroscopy as an ideal tool for speciation studies in complex systems, particularly those relevant to the nuclear fuel cycle. In this review, we present an overview of the developments and applications of CmIII luminescence spectroscopy in the last 20 years since the last comprehensive review was published. The discussed studies have been categorized according to their chemical environment into reactions at the water/mineral interface, studies of solids containing CmIII, aqueous complexation studies, spectroscopy in non-aqueous systems, and interaction of CmIII with biomolecules and biota. These systems correlate in large parts with areas of application in nuclear waste disposal science, separation processes within current and proposed nuclear fuel cycles, and radioecological research. We summarize the most important findings in the studies, identify emerging trends and persistent challenges in the field of CmIII luminescence spectroscopy. Finally, we offer an outlook on potential future developments and research directions in this area.